Remarks by World Bank Group President David Malpass at the WHO Ministerial Briefing on the Global COVID-19 Vaccination Strategy and Implementation - Malpass, David (World Bank, Washington, DC, 2022)
These remarks were delivered by World Bank Group President David Malpass at the WHO Ministerial briefing on the Global Coronavirus (COVID-19) Vaccination Strategy and Implementation on July 21, 2022. He said that over the past months, much of the world’s attention has shifted to Russia’s invasion of Ukraine and the risks it poses to global supplies of energy and food. He added that we are simultaneously facing many other crises, including the sharp rise in inflation and poverty, climate, the learning losses from school closures, and more countries facing conflicts and violence. He mentioned that even as the virus has continued to mutate, vaccines remain highly effective at reducing serious illness and death. He highlighted that the World Bank has supported developing countries with COVID-19 emergency health and vaccine operations in more than 100 countries amounting to over fourteen billion. He spoke about their vaccine financing is helping countries purchase and distribute vaccines, expand storage and cold chains, develop tracking systems, train health workers, engage citizens and communities, and strengthen health systems. He gave three examples of the Bank’s efforts in supporting countries: Bangladesh, Uganda, and Liberia. He said that World Bank Group has also been working through World Bank-financed projects and through the Global Financing Facility platform to provide financing and prioritization of primary health care systems that will deliver immunization and other essential services. He also mentioned about ongoing efforts to provide additional financing to address critical gaps in pandemic prevention, preparedness, and response (PPR). Finally, he concluded by inviting all member States to continue collaborating to bring the COVID-19 pandemic to its end, including vaccinating the most vulnerable, and work together to build stronger, resilient health systems that are ready to prevent, detect and respond to future emergencies.